High-temperature redox chemistry of La1.5+xSr0.5-xCo0.5Ni0.5O4+delta (x=0.0, 0.2) studied in situ by neutron diffraction - Tonus, F; Greaves, C; El Shinawi, H; Hansen, T; Hernandez, O; Battle, P; Bahout, M (2011)
Neutron powder diffraction has been used to investigate the redox behaviour of two n = 1 Ruddlesden-Popper (RP) oxides, La1.5+xSr 0.5-xCo0.5Ni0.5O4+δ (x = 0.0, 0.2) in situ and in real time during cycling through the temperature range 20 < T/°C < 600 under flowing 5% H2. Both compositions retained I4/mmm symmetry throughout the heating and cooling cycle. Rietveld refinement of data collected at room temperature showed the presence of interstitial oxygen in the original samples (δ ≈ 0.06(1) and 0.12(1) for x = 0.0 and 0.2, respectively). When heated in flowing H2, both compositions were reduced over the temperature range 300 < T/°C < 600 (δ ≈ -0.22(2) and -0.06(2) for x = 0.0 and 0.2, respectively). In the case of the x = 0.2 material, reduction clearly occurred first at the interstitial site (Oint), then at the equatorial site (O eq). The changes in composition were accompanied by changes in unit-cell parameters and bond lengths. Rietveld refinements revealed residual partial occupation of the Oint site in the reduced x = 0.2 sample. This is the first structural evidence of the coexistence of both anion vacancies and interstitial anions in a hypostoichiometric n = 1 RP oxide. The temperature dependence of the atomic displacement parameters is consistent with the presence of local rotations of the anion-deficient coordination polyhedra. On heating the reduced x = 0.2 material in an O2 flow, the refilling of both the Oeq and Oint sites began at 200 °C and the stoichiometry of the original as-prepared sample was recovered by 250 °C. © 2011 The Royal Society of Chemistry.